Using a Plant Tour to Help Teach Job Order Costing - Creel, Timothy; Paz, Veronica; Olear, Christine (Journal of Accounting and Finance, 2021)
A plant tour offers accounting students the ability to see what they are studying in managerial or cost accounting in a real-world business setting. A tour of the Nissan plant in Smyrna, Tennessee is discussed in this paper. The students enjoy the field trip and expressed positive feelings about the experience of learning accounting material outside the classroom. While in the plant, students see many elements of managerial or cost accounting after discussing them in class, including job order costing and the aspects of the product cost. A virtual tour can take the place of a physical plant tour.